Semiconducting Polymer Nanoparticles with Persistent Near-infrared Luminescence Show Potential for In Vivo Optical Imaging() - Palner, Mikael (Angew Chem Int Ed Engl, 2015)
Materials with persistent luminescence are attractive for in vivo optical imaging since they have a long lifetime that allows the separation of excitation of fluorophores and image acquisition for time-delay imaging, thus eliminating tissue autofluorescence associated with fluorescence imaging. Persistently luminescent nanoparticles have previously been fabricated from toxic rare-earth metals. This work reports that nanoparticles made of the conjugated polymer MEH-PPV can generate luminescence persisting for an hour long upon single excitation. A near-infrared dye was encapsulated in the conjugated polymer nanoparticle to successfully generate persistent near-infrared luminescence through resonance energy transfer. This new persistent luminescence nanoparticles have been demonstrated for optical imaging applications in living mice.